A Complex Approach to Liver Protection from Mycotoxicoses in Experimental Conditions (Asian Journal of Pharmaceutics (AJP), 2019)
Aim and Objective: The main objective of this study was the research of the protective effect of a complex biologically active additive containing dietary fiber and lecithin on the model of associative mycotoxicosis reproduced on laboratory animals. Materials and Methods: Experimental modeling of chronic associative mycotoxicosis was performed on 30 male rats, divided into three groups of 10 individuals each. The essence of the method for the reproduction of associative mycotoxicosis was that for 30 days, the rats of the first and second experimental groups were fed with the feed that was naturally contaminated with mycotoxins. The rats of the firstexperimental group were additionally supplemented daily per os with a complex biologically active additive in a dosage of 1.5 g per animal. The rats of the second experimental group were fed only with toxic feed. The third group of rats served as a biological control, receiving benign mixed feed. The effectiveness of the protective action of the additive was estimated by the survival rate of rats, gravimetric body weight, clinical signs, and changes in biochemical blood factors. Results: Application of the complex additive consisting of product processing plant raw materials - sugar beet pulp and rapeseed lecithin (in the ratio 4:1) on the background of feeding rats with the feed, contaminated with mycotoxins (association T-2 toxin, zearalenone, and aflatoxin B1), leads to a weakening of the action of xenobiotics that are manifested by improvement of biochemical homeostasis and functional state of liver of the experimental animals. Conclusion: The conducted studies have shown that the use of plant dietary fibers in combination with phospholipids of lecithins on the laboratory background of mycotoxicosis results in weakening of xenobiotic action, which is manifested by improvement of biochemical homeostasis and liver functional status of experimental rats, increasing their safety, and decreasing clinical manifestations of intoxication.